2015
DOI: 10.1111/eos.12200
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐adherence and bactericidal activity of sphingolipids against Streptococcus mutans

Abstract: This study evaluated the anti-biofilm activity of sphingosine, phytosphingosine (PHS), and sphinganine for: (i) anti-adherence activity on hydroxyapatite (HA) surfaces; and (ii) bactericidal activity on different Streptococcus mutans phenotypes (i.e. planktonic cells and cells from a disrupted biofilm). For this, HA discs treated with sphingolipids were incubated with S. mutans and the number of adherent cells was evaluated by both culture and confocal microscopy. Sphinganine strongly inhibited bacterial adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 26 publications
2
58
1
Order By: Relevance
“…We are aware that the experimental models we used in this study are limited artificial models which only partly represent some aspects of the in vivo situation. In the current study glass surfaces were used instead of hydroxyapatite, in contrast to earlier studies [Cukkemane et al, 2015;Valentijn-Benz et al, 2015;Yonel et al, 2016]. Although this might be considered as a limitation of the study, it did enable the use of real-time imaging in the BioFlux experiments for visual monitoring of the effects of PHS in a dynamic setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We are aware that the experimental models we used in this study are limited artificial models which only partly represent some aspects of the in vivo situation. In the current study glass surfaces were used instead of hydroxyapatite, in contrast to earlier studies [Cukkemane et al, 2015;Valentijn-Benz et al, 2015;Yonel et al, 2016]. Although this might be considered as a limitation of the study, it did enable the use of real-time imaging in the BioFlux experiments for visual monitoring of the effects of PHS in a dynamic setting.…”
Section: Discussionmentioning
confidence: 99%
“…This model consists of a custom-made stainless steel lid with 24 clamps that hold the untreated and PHS-treated glass cover slips used as a substratum for the bacterial adhesion. For the anti-adhesive experiments, sterile glass cover slips were treated with PHS in a Tris-Tween buffer as described by Cukkemane et al [2015]. As control, glass cover slides were treated with Tris-Tween buffer only.…”
Section: In Vitro Anti-adhesive and Anti-biofilm Effects Of Phs In A mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been recently reported that the pre-treatment of experimental hydroxyapatite (HAp) discs with sphingoid bases such as sphingosine, phytosphingosine (PHS), PHS phosphate and sphinganine significantly protected HAp against acid demineralisation in vitro [Valentijn-Benz et al, 2015] . Cukkemane et al [2015], using atomic force microscopy, reported that PHS and other sphingoid bases have the ability to form diffusion barriers against H + ions and bacteria. In principle, the reported anti-erosive properties would suggest that PHS could be included in oral care products for the management and treatment of DH.…”
mentioning
confidence: 99%